Precipitation hardening of Cu-Ti-Zr alloys - Markandeya R.; Nagarjuna S.; Sarma D.S. (My University, 2025)
The influence of age hardening temperature and time on the hardness, tensile properties, electrical conductivity, and microstructure of Cu-4Ti-0.1Zr and Cu-3Ti-0.1Zr alloys has been investigated. The resulting microstructure of these alloys suggests that zirconium addition prohibited the formation of compositional modulations in the solution treated condition. These alloys exhibited maximum hardness and strength on peak aging at 45O°C for 24 h by the formation of a coherent and metastable Cu4Ti phase (β′) in modulated structure while overaging occurred by the formation of equilibrium phase β-Cu3Ti. The electrical conductivity of both the alloys increased moderately on aging. Unlike in an earlier study of binary Cu-Ti and some ternary Cu-Ti-X alloys, overaging did not cause any discontinuous precipitation in the Cu-Ti-Zr alloys investigated. Modulated structure formed on peak aging persisted on prolonged aging at 45O°C for 80 h or at 500°C for 8 h.